EMERGENCE OF CLASSES AND SOCIAL STRATIFICATION: AN ANALYSIS OF PRE-COLONIAL AND COLONIAL LAHORE - Dr. Ahmad Hassan (International Journal of Contemporary Issues in Social Sciences, 2024)
This research is aimed at studying the emergence of classes and social stratification of pre-colonial and colonial South Asia through the case study of Lahore, the capital city of the Pakistani Punjab. Through employing the theoretical model of Wright (2003) about class categorization, based on Marxist and Weberian notions of class, this research postulates that South Asian society have evolved through pre-colonial subjective position to colonial objective and relational positions, leading to historical foundation. The central argument maintains that before colonial intervention the daily life and society of Lahore was not divided into economic sections and classes and was collectivist in nature. With the advent of British rulers the society was starkly divided into categories and sections, making them exclusive from inclusive. This compartmentalization of the society was primarily based on economy, resulting in the emergence of classes, i.e. elite, middle, lower, upper and lower middle, and under the poverty line. This research is a qualitative analysis built upon archival materials and secondary sources.